Estudos das vias de sinalização mobilizadas pela cepa G de Trypanosoma cruzi na invasão celular, da sinalização intracelular ativada pela proteína P21-HIS6 e seu renovelamento - Santos, Marlus Alves dos (2013)
Trypanosoma cruzi is the etiologic agent of Chagas disease, which induces a pathological hypertrophy in the heart, esophagus and colon. This disease affects millions of peoples in Latin America. Recently our group characterized a 21 kDa T. cruzi recombinant protein (P21-His6) based on native form secreted by T. cruzi. P21-His6 is purified from insoluble inclusion bodies or soluble fraction from bacterial extract. The protein obtained from each protocol has identical secondary structure and was capable of inducing parasite phagocytosis and increased zymosan particles internalization by macrophages cell being that process PI3 kinase signaling pathway dependent. In addition the refolding protocol generates of high amounts of the recombinant protein. Also we investigated the signaling pathway involved in amastigotes and trypomastigotes (living, dead and opsonized) T. cruzi developmental stages invasion using macrophages treated or not with signaling pathway inhibitors drugs. Opsonized parasites are internalized a lot. Living amastigotes triggered PI3K and MAPK signaling pathways, dead amastigotes activated only MAPKs pathway. Living and dead trypomastigotes activated all the signaling pathways studied.